Comparative Study and evolution of Mobile Banking Security Solutions and Comparision between Various Solutions - Malik, Mubina; Banker, Shreya (International Journal of Computer Sciences and Engineering, 2019)
Due to the rapidly increasing use of mobile phones, it is essential to provide a secure solution for mobile phones; with the evolution of mobile commerce, it is obvious to provide a secure and efficient solution for the mobile environment. Day by day usages of mobile devices is huge and consumers are getting familiar with the various purposes of devices such as mobile banking. This paper focuses and describes various types of mobile banking methods and their possible security solutions. In the first part mobile banking solutions using contactless technology – Near Field Communication (NFC) is discussed with its limitations in terms of security. In addition, we also address the security weaknesses of Wireless Application Protocol (WAP) and Wireless Transport Layer Security (WTLS). To overcome the above mention weaknesses, in the second part different solutions of mobile banking with Public Key Infrastructure such as MPKI, WPKI, ECC, LPKI are discussed with its limitations and possible solutions to overcome the limitations.